2020
DOI: 10.1186/s12874-020-01182-w
|View full text |Cite
|
Sign up to set email alerts
|

On Jones et al.’s method for extending Bland-Altman plots to limits of agreement with the mean for multiple observers

Abstract: Background To assess the agreement of continuous measurements between a number of observers, Jones et al. introduced limits of agreement with the mean (LOAM) for multiple observers, representing how much an individual observer can deviate from the mean measurement of all observers. Besides the graphical visualisation of LOAM, suggested by Jones et al., it is desirable to supply LOAM with confidence intervals and to extend the method to the case of multiple measurements per observer. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…A consequence of this greater similarity would be a decrease in the uncertainty and, therefore, a decrease in the CI widths. A peculiarity of the computational procedure by Christensen et al is that σ̂ normalB 2 can be negative, which we see in three of the samples in Table S2. Using the ICC( A ,1) values to back-calculate the value of σ̂ normalB 2 , we found σ̂ normalB 2 values between −2 × 10 –4 and −9 × 10 –4 , suggesting that their σ̂ normalB 2 are probably close to zero for these cases (GR-Q, DE, and CA-Q).…”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations
“…A consequence of this greater similarity would be a decrease in the uncertainty and, therefore, a decrease in the CI widths. A peculiarity of the computational procedure by Christensen et al is that σ̂ normalB 2 can be negative, which we see in three of the samples in Table S2. Using the ICC( A ,1) values to back-calculate the value of σ̂ normalB 2 , we found σ̂ normalB 2 values between −2 × 10 –4 and −9 × 10 –4 , suggesting that their σ̂ normalB 2 are probably close to zero for these cases (GR-Q, DE, and CA-Q).…”
Section: Resultsmentioning
confidence: 81%
“…A consequence of this greater similarity would be a decrease in the uncertainty and, therefore, a decrease in the CI widths. A peculiarity of the computational procedure by Christensen et al 34 is that B 2 can be negative, which we see in three of the samples in Table S2. Using the ICC(A,1) values to back-calculate the value of From Table S2, we found that pollen-free DNA analyses yielded fewer N − 1 genera relative to their pollen DNA counterparts, indicating that pollen-free DNA approaches are more variable across replicates.…”
Section: ■ Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…When the LoA are smaller than a given tolerance (differences small enough to be considered clinically unimportant) the two techniques are assumed to have acceptable equivalence [9,10,11]. More recently, confidence intervals were added around the upper and lower LoA [12,13,14,15]. Although providing a little more room for the tolerance, LoAs may be regarded as a statistical test for the band limits but do not provide any decision for the technique's equivalence.…”
Section: Introductionmentioning
confidence: 99%